ANALISIS RASIO KEUANGAN SEBAGAI ALAT UNTUK MENGUKUR KINERJA KEUANGAN PADA PT. BENTOEL INTERNASIONAL INVESTAMA Tbk PERIODE 2018-2019 - E Y Suharyono 3, Syafitri Eka Setyawati Eka Yudhyani 2 (EKONOMIA, 2021)
The results of financial ratio analysis are 1.) Financial performance in terms of the Liquidity Ratio (Current Ratio) of PT Bentoel Internasional Investama Tbk in 2019 experienced good conditions compared to 2018, so hypothesis 1 (one) is accepted. 2.) Financial performance in terms of the Liquidity Ratio (Quick Ratio) of PT Bentoel Internasional Investama Tbk in 2019 experienced good conditions compared to 2018, so hypothesis 2 (two) is accepted. 3.) Financial performance in terms of the Liquidity Ratio (Cash Ratio) of PT Bentoel Internasional Investama Tbk in 2019 experienced poor conditions compared to 2018, so hypothesis 3 (three) is rejected. 4.) Financial performance in terms of the Profitability Ratio (Net Profit margin) of PT Bentoel Internasional Investama Tbk in 2019 experienced bad conditions compared to 2018, so hypothesis 4 (four) was rejected. 5.) Financial performance in terms of Profitability Ratios (Return On Assets) of PT Bentoel Internasional Investama Tbk in 2019 experienced poor conditions compared to 2018, so hypothesis 5 (five) was rejected. 6.) The financial performance in terms of the Profitability Ratio (Return On Equity) of PT Bentoel Internasional Investama Tbk in 2019 experienced bad conditions compared to 2018, so hypothesis 6 (six) was rejected. 7.) Financial performance in terms of the Solvency Ratio (Debt To Equity Ratio) PT Bentoel Internasional Investama Tbk in 2019 experienced poor conditions compared to 2018, so hypothesis 7 (seven) was rejected. 8.) Financial performance in terms of the Solvency Ratio (Debt To Asset Ratio) of PT Bentoel Internasional Investama Tbk in 2019 experienced bad conditions compared to 2018 so hypothesis 8 (eight) was rejected.